2020
DOI: 10.1177/0954008320908652
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically heat-sealable polyimide films with atomic oxygen resistance: Synthesis and characterization

Abstract: Intrinsically heat-sealable polyimides with atomic oxygen (AO) resistance (ARPIs) were synthesized from 2,3,3′,4′-oxydiphthalic anhydride (aODPA), 2,5-bis[(4-aminophenoxy)phenyl]diphenylphosphine oxide (BADPO), and para-phenylenediamine (PDA). The effects of the molecular structure and diamine ratio were investigated on the properties of the ARPI, including mechanical property, thermal property, heat sealability, and AO resistance. Heat sealability and AO resistance were realized for the ARPI film by combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…It was also found that CPI-0 has a lower AO erosion yield than Kapton HN, which was similar to PI (aODPA-PDA) and Kapton HN. 36 There are several steps involved in the AO exposure process for a polymer, including erosion initiation by oxygen atom-surface interaction, erosion propagation by chain scission, and material loss due to volatile removal. 45 Among the three steps, the first two are dominated by chemical interactions, and the last one by physical interaction such as AO collisions with the volatile species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that CPI-0 has a lower AO erosion yield than Kapton HN, which was similar to PI (aODPA-PDA) and Kapton HN. 36 There are several steps involved in the AO exposure process for a polymer, including erosion initiation by oxygen atom-surface interaction, erosion propagation by chain scission, and material loss due to volatile removal. 45 Among the three steps, the first two are dominated by chemical interactions, and the last one by physical interaction such as AO collisions with the volatile species.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, AO resistance was realized for the aODPA-( para -phenylenediamine) (PDA) system by introducing DPO comonomer. 36 This work is aimed at developing heat-sealable polyimide films with enhanced AO resistance and mechanical strength for aerospace applications. These polyimides were prepared via copolymerizing 4,4′-oxydianiline (ODA), BADPO and aODPA.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, two PI references, including PI‐ref‐a (HPMDA‐ODA) and PI‐ref‐b (HBPDA‐ODA) were also prepared via the similar procedure. The phosphorus‐containing diamine, BADPO was developed in our laboratory and mass‐produced for the research and development of functional PI films, such as the PI films with excellent atomic oxygen resistance, 31,32 with good heat‐processability, 33 and so on. Actually, phosphorus‐containing diamines have been well used as highly‐efficient FRs for the common combustible polymers, such as epoxy 34 due to the flame retardant functionality of phosphorus components both in gas phase and condensed phase 35 .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that via adding a third monomer containing flexible segments, bulky groups and non-coplanar structures during copolymerization, these structures can be incorporated into the molecular chain of polyimides, thereby effectively improving their solubility and processability. [19][20][21][22][23] In the late 1970s, the Langley Research Center of NASA introduced thermoplastic polyimide under the name ''LARC-TPI''. 24,25 Since then, thermoplastic polyimides have attracted extensive research attention.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, different structural modifications were carried out to improve the solubility and processing characteristics of aromatic polyimides. It is well known that via adding a third monomer containing flexible segments, bulky groups and non‐coplanar structures during copolymerization, these structures can be incorporated into the molecular chain of polyimides, thereby effectively improving their solubility and processability 19–23 . In the late 1970s, the Langley Research Center of NASA introduced thermoplastic polyimide under the name ''LARC‐TPI'' 24,25 .…”
Section: Introductionmentioning
confidence: 99%